BIMBINGAN TEKNIS PENGOLAHAN LIMBAH CAIR INDUSTRI TAHU DI SENTRA INDUSTRI TAHU TEGALPASANGAN – PAKIS – MALANG - Prayitno Prayitno; Sri Rulianah; Windi Zamrudy (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2020)
The tofu industrial center of Tegalpasangan - Pakis - Malang is one of the large tofu industrial centers in Malang Regency, where in the tofu industrial center there are no less than 20 tofu industries, most of which are Micro, Small and Medium Enterprises (MSMEs) with a workforce of 2 - 4 people with an average production capacity of 2-5 quintals of soybeans per day. Like other cottage industries, tofu is produced manually without mechanical equipment, and there is little attention to good, healthy production methods. Likewise, without the existence of a wastewater treatment plant (IPAL) to treat waste water generated from the production process, which results in pollution of the aquatic environment. Community service activities aim to increase the knowledge, understanding and skills of partners (tofu industry owners) in producing tofu and treating wastewater properly and healthily. Technical guidance is provided in the form of GMP (Good Manufacturing Product) training, HACCP (Hazard Analitycal and Critical Control Point), waste treatment and provision (grant) of WWTP equipment. The results of PkM activities show that the provision of training and IPAL grants provides significant benefits for the knowledge and skills of partners, especially in handling waste water produced from the tofu industry so that it can reduce environmental pollution.